IMPERFECT REPAIR STRATEGY UNDER TWO-DIMENSIONAL WARRANTY BASED ON PRODUCTÃâÃâS USAGE RATE - MEDINA INDASARI MASJHUR (NIM: 23406062); Dosen Pembimbing : Prof. Dr. Ir. Bermawi P. Iskandar, PUTI
Products sold with warranty mean additional costs (called warranty cost) to the manufacturer to service any claims. The warranty cost can significantly influence the price of the products. This warranty cost can be reduced by three ways Ã‚Â– i.e. improving product reliability, use of preventive maintenance, and warranty servicing strategy. In this thesis, two serving strategies are defined and studied for repairable items sold with a two-dimensional warranty. For repairable items, the manufacturer has the option to rectify the failed item, either to replace with a new one or to repair it. If the cost of replacement is high, an imperfect repair instead of a replacement is more economical. In the strategies studied, the warranty region is divided into three sub-regions, where the middle region does not restrict to L-shape and the first failure occurred in this subregion will be rectified with imperfect repair. All other failures will be minimally repaired. An accelerated Failure Time (AFT) model is used to allow for the effect of usage rate on item degradation. Finally, some numerical examples are given to illustrate the optimal solutions for the two strategies studied.